Are physical activity and sedentary behavior patterns contributing to diabetes and metabolic syndrome simultaneously?. Issue 2 (10th December 2020) - Colpitts, Benjamin H.; Smith, Spencer; Bouchard, Danielle R.; Boudreau, Jonathan; Sénéchal, Martin
Abstract: To investigate cross‐sectional association between sedentary activities and moderate‐to‐vigorous physical activities' (MVPA) patterns, and the likelihood of having diabetes, MetS, or both conditions. This cross‐sectional analysis from the National Health and Nutrition Examination Survey 2003‐2004 and 2005‐2006 cycles included 2456 adults. The primary exposure variables were sedentary and MVPA patterns (1‐, 5‐, 10‐, 30‐, and 60‐minute bouts) measured by accelerometer. The primary outcome measure was the subgroup categorization: healthy group, MetS group, diabetes group, and Mets & diabetes group. No differences were observed regarding proportion of sedentary patterns among groups, but differences were observed for the proportion of time spent doing MVPA in 5‐, 10‐, and 30‐minute bouts among groups (all P < .05). When comparing individuals having both MetS & diabetes to the MetS group and the diabetes group, all bout lengths of sedentary behavior were significantly different ( P < .05). The patterns of sedentary behavior were not associated with higher odds of being classified with Mets & diabetes when adjusted for total MVPA time (all P > .05). Interestingly, the odds of being in the healthy group were associated with MVPA patterns following adjustment for total sedentary time. The findings suggest it is more important to focus on exercise performed at moderate‐to‐vigorous intensity, of any bout length, compared to sitting less to lower the odds of MetS and diabetes.